DIMENSI NILAI JASA BANK TERHADAP KEPUASAN NASABAH DAN DAMPAKNYA PADA LOYALITAS (STUDI PADA BANK BCA CABANG SURABAYA) - Danny Wibowo (Institute of Research and Community Outreach - Petra Christian University, 2012)
The purpose of this study is to investigate and analyze the effect of directly or indirectly between dimensions variable value of bank services (interest rates, facilities, employees, obligations, the process, a sense of security and benefits) to the loyalty of the customer satisfaction variables mediate Bank BCA Darmo Branch Surabaya. Type of research is primary data is data obtained from the results of observations, interviews and meetings with the object as well as the respondents' answers on questionnaires distributed and secondary data, the data obtained from the company's internal data, journals, books related to the object research. Method of collecting data by conducting field research aimed at gaining empirical data to test the hypothesis. Analysis approach in this study is quantitative. The study results showed two stage least square analysis showed that the dimensional value of bank services direct effect on customer loyalty and indirect effect can also (bank service value dimensions influence customer loyalty is mediated by customer satisfaction variable).